Effect of ginger to overcome nausea and vomiting in pregnant women: a narrative review - Ferila Adiesti; Sulasmi -; Shelly Rodliah Rosyad; Novia DwiJayanti; Melia Dwi Yitna (Journal of Health Technology Assessment in Midwifery, 2021)
Background: Nausea, and vomiting (emesis gravidarum) are symptoms that often occur in 60-80% primigravida and 40-60% multigravida. Nausea and vomiting are symptoms experienced by women during early pregnancy, where this condition usually begins 4-8 weeks of pregnancy and can be more severe by the 9th week. The condition of nausea and vomiting will improve at 14 weeks of gestation and above. The discovery of the effectiveness of ginger in reducing nausea and vomiting in pregnancy is a potential health technology assessment that can be recommended in midwifery practice. However, a comprehensive analysis is needed regarding the use of ginger in reducing complaints of nausea and vomiting in pregnancy. Therefore, this analysis was conducted to determine how the effect and safetyness of ginger in reducing nausea and vomiting in pregnancy.